1964
DOI: 10.1021/ac60207a057
|View full text |Cite
|
Sign up to set email alerts
|

Low-Voltage Sensitivities of Aromatic Hydrocarbons.

Abstract: b A new set of low-voltage calibration data is presented for aromatic hydrocarbons, including compound types from alkylbenzenes to chrysenes. Separate data are provided for alkylbenzenes with different degrees of substitution and for average coefficients for these compound types obtained by using detlmnined and calculated average isomeric distribution values. Ionization-efficiency curves also have been obtciined for a number of alkylbenzenes in an effort to correlate ion current magnitudes at a given ionizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 5 publications
3
29
0
Order By: Relevance
“…, / for each value of a,b, and c, and η = 4 or 3 for even or odd values of a, respectively. The available data indicate that the mole sensitivities, s(my)<, for ionization of aromatic compounds of present interest by both low-voltage electrons (44,45) and high-electric fields (46) …”
Section: Methodsmentioning
confidence: 99%
“…, / for each value of a,b, and c, and η = 4 or 3 for even or odd values of a, respectively. The available data indicate that the mole sensitivities, s(my)<, for ionization of aromatic compounds of present interest by both low-voltage electrons (44,45) and high-electric fields (46) …”
Section: Methodsmentioning
confidence: 99%
“…It was quickly realized that the 70 eV ionization voltage was causing extensive fragmentation and gave no differentiation between different classes of compounds. Low voltage approaches were developed in order to selectively ionize certain classes of hydrocarbons, particularly olefins [16] or aromatics [17]. The lower ionizing voltage significantly reduced fragmentation allowing more high mass ions to be detected.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…The advantages of low energy ionization can readily be seen when comparing low voltage electron impact (EI) with 7Q.-eV El. Low voltage mass spectrometry has been used for several decades to simplify the mass spectra of complex mixtures of unsaturated compounds, as would be encountered with fossil fuel samples [16][17][18][19]. More recently, Maccoll and co-workers [20][21][22][23][24][25][26][27][28][29][30][31] have shown that 12-eV EI mass spectra of aliphatic compounds contain much higher molecular ion abundances and more structurally significant fragmentation than 7Q.-eV EI.…”
mentioning
confidence: 99%